Shortening tends to increase aortic foam cell count and wall thickness in male Wistar rats - Lusiantari, Rokhima; Pramaningtyas, Miranti Dewi; Nurmasitoh, Titis; Pattimura, Rachmi Hidayati; Dewanti, Anggita (Faculty of Medicine, Trisakti University, 2018)
BackgroundShortening is widely used as raw material for bread and other foods. Hypercholesterolemia increases aortic arch foam cell formation and abdominal aortic wall thickness. This study aimed to determine the effect of shortening on the number of aortic arch foam cells and abdominal aortic wall thickness in rats.MethodsThis study was of experimental posttest control group design. Twenty four male Wistar rats were randomized into 4 groups. The negative control group (C-) received standard feed, the positive control group (C+) standard high-fat feed, group T1 shortening and standard feed at a ratio of 1:5 and group T2 shortening and standard feed at a ratio of 1:10. The interventions were given for 6 weeks through gavage. The foam cell count in the aortic arch and the thickness of the abdominal aortic wall were measured. One-way ANOVA test was used to analyze the data. ResultsThere was no significant difference in the mean foam cell count of the aortic arch between the four groups C- (7.17 ± 4.17), C + (9.33 ± 7.01), T1 (11.83 ± 4.88) and T2 (9.33 ± 6.80) (p=0.598). The mean thickness of the abdominal aortic wall between the four groups C- (741.98 ± 60.67μm), C + (714.29 ± 90.59μm), T1 (838.90 ± 75.86 μm), and T2 (749.88 ± 99.37μm) also was not significantly different (p=0.110).Conclusion Shortening tends to increase the foam cell count of the aortic arch and the thickness of the abdominal aortic wall of rats.